Morphological and Molecular Detection of Oestrus ovis Isolated from Goats in Babylon Province, Iraq - Adhem, Noor-Aldeen; Kreem, Safaa M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Oestrosis caused by Oestrus ovis is a very impactful illness for the small ruminant industry in Iraq, resulting in substantial economic losses. The present study was conducted to characterize Oestrus ovis of Larvae morphologically and molecularly from goat at a slaughter house in Babylon province, Iraq. The study relied on the collection of 50 larvae at various developmental stages between November 2023, and March 2024. The morphological analysis was conducted with a stereomicroscope depend on distinct larval traits such as the dorsal and ventral position, spiracles, hooks, and cephalopharyngeal skeleton. The molecular characterization involved PCR and PGS techniques on the COX1 gene, focusing on a 330-bp section. In terms of morphology, the L1 larvae had unique mouth hooks, while the L2 larvae showed noticeable terminal stigmas. The most important traits of the L3 were the colour of their body parts and the existence of the spines. PCR analysis showed successful amplification at 330bp regions in 12 isolates. The PGS analysis found 12 unique local isolates that have genetic similarities with isolates from Spain and Czech Republic. In conclusion, this study highlights the significant important of Oestrus ovis in goats in Babylon province, Iraq.